Preeklampsia pada Ibu Bersalin di RSUD Kota Baubau: Sebuah Kajian Multifaktorial - Nursafitri Anhufi; Wa Ode Salma; Jafriati Jafriati (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Preeclampsia is one of the pregnancy complications that contributes significantly to the increasing maternal and infant morbidity and mortality rates, particularly in developing countries. In Baubau City, preeclampsia remains a common health problem and has the potential to cause serious complications if not managed appropriately. This study aimed to analyze the determinants of preeclampsia among housewives in the Delivery Room of Baubau City Regional General Hospital in 2025. This study employed a quantitative approach with a cross-sectional design. The study population consisted of all mothers diagnosed with preeclampsia who were treated in the Delivery Room of Baubau City Regional General Hospital. The sampling technique used was total sampling, involving 65 respondents. The data used were secondary data obtained from patients’ medical records. The dependent variable was the incidence of preeclampsia, while the independent variables included maternal age, parity, maternal disease history, family disease history, and maternal education level. Data analysis was performed using the chi-square test and multivariate logistic regression. The results showed that there was no significant relationship between maternal age (p-value = 0.689), parity (p-value = 0.304), maternal disease history (p-value = 0.161), family disease history (p-value = 0.161), and maternal education level (p-value = 0.706) with the incidence of preeclampsia. The logistic regression analysis also indicated that none of the independent variables had a significant effect on the incidence of preeclampsia, although maternal disease history tended to increase the risk. The conclusion of this study indicates that the incidence of preeclampsia is not influenced by a single specific factor but is multifactorial in nature. Therefore, early detection efforts and comprehensive pregnancy monitoring are necessary to prevent more severe complications.